Estimating the Base of the Value-Added Tax (VAT) in Developing Countries : The Problem of Exemptions - Mackenzie, George (IMF Working Papers; Working Paper, 1991)
Developing countries with VATs typically exempt a large number of goods and services. Following a brief discussion of the rationale for exemptions, this paper presents a formula for the base of a VAT with exemptions. Two basic adjustments must be made to the base without exemptions: subtraction of the value of sales to consumers of exempt industries and addition of intermediate sales of taxable inputs to exempt industries. The paper concludes with a derivation of the elasticity of a VAT with exemptions with respect to aggregate consumption and a discussion of the implications of technological change for the VAT base.